A Targeted Screening Program for Latent Tuberculosis Infection Among Hematopoietic Cell Transplant Recipients. (10th June 2020) - Sosa-Moreno, Andrea; Narita, Masahiro; Spitters, Christopher; Swetky, Michelle; Podczervinski, Sara; Lind, Margaret L; Holmberg, Leona; Liu, Catherine; Edelstein, Raleigh; Pergam, Steven A
Abstract: Background: US hematopoietic cell transplantation (HCT) recipients have a low prevalence of latent tuberculosis infection (LTBI), but if latently infected they are at risk for progression to active tuberculosis. At our center, all HCT recipients underwent LTBI testing pretransplant by tuberculin skin testing (TST) until 2013 when we implemented a targeted screening program. Our objective was to assess the utility of our screening program that incorporated a pretransplant LTBI questionnaire to target TST and QuantiFERON TB Gold (QFT) testing. Methods: We performed a retrospective cohort study of HCT recipients undergoing first transplant from 2014 to 2016. Patients with positive, indeterminate, and a subset with negative QFT results underwent electronic medical record (EMR) review to assess TST results and risk factors for LTBI. Results: Among 1290 eligible recipients, 457 (35%) had at least 1 risk factor for LTBI on the pretransplant questionnaire; nonwhites were more likely to undergo LTBI testing ( P  < .0001). Overall, 16 of 1290 (1.2%) had at least 1 positive LTBI test. Of those screened by QFT, 14 of 457 (3%) were positive and 52 (11%) were indeterminate. Among those undergoing EMR review, 123 of 267 (46%) had TST records; 4 of 123 (3%) positive by both TST and QFT, and 2 (2%) by TST alone. Two or more risk factors were reported among the majority of LTBI-positive patients (15 of 16 [94%]). All patients with at least 1 positive test for LTBI (n = 16) were evaluated, and 11 of 16 (69%) were recommended to receive treatment. Conclusions: Incorporating a pretransplant LTBI questionnaire allowed for an approximate 65% reduction in LTBI testing when compared with universal testing among this low prevalence population. Abstract : Hematopoietic cell transplantation in the United States has a low population prevalence for latent tuberculosis infection. A pretransplant latent tuberculosis (LTBI) questionnaire allowed for an approximate 65% reduction in LTBI testing when compared with universal screening. Visual Abstract: